Os ludolinguistas e as frases de duplo sentido: algumas notas de leitura - Coelho, Bruna Cristina de Souza (Universidade Federal de São Carlos, 2024)
Paveau (2008; 2018 and 2020) identifies four types of linguistic practice by non-linguists: descriptive, prescriptive, interventionist and militant. And, eschewing Cartesian binarism - linguists versus non-linguists - he proposes a classification of folk linguistics practitioners, based on "a continuum between those who make linguistics a single science and those who do not" (PAVEAU, 2018, p. 24-25). In descending order of mastery of specialized linguistic knowledge, the continuum goes from the professional linguist, the language scientist, to the common man. Paveau (2008) considers non-linguists to include, for example, ludolinguists - social actors who (in)consciously produce knowledge with and about language and language. Based on the typology proposed by Paveau (2008; 2018 and 2020), we seek to discursively deepen a particular type of work by ludolinguists, which is the production and circulation of double-meaning phrases. For this study, we selected phrases of a malicious nature. We are interested in observing how it is possible for non-linguists to produce linguistic knowledge, presenting folk knowledge as practical and useful knowledge that helps speakers to maintain and/or transform society. We start from the anti-eliminationist position proposed by the French theorist: "Folk statements are not necessarily false, mistaken beliefs to be eliminated from science. On the contrary, they constitute perceptive, subjective and incomplete knowledge to be integrated into the scientific data of linguistics" (PAVEAU, 2008, p. 8)". Thus, we also sought to ascertain to what extent the pre-discourses (shared beliefs and knowledge) inscribed in the linguistic materiality of these sentences irrigate the discursive memory of their production and circulation, bringing out knowledge that registers and engenders belonging or estrangement in relation to other discourses, for example, sexist discourse, taboo discourses related to sex, homosexuality, religion, work, etc.
Les ludolinguistes et les phrases à double sens: quelques notes de lecture
Keywords: Linguística popular; Discurso; Frases de duplo sentido; LINGUISTICA, LETRAS E ARTES::LINGUISTICA